2017
DOI: 10.1186/s40101-017-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic time series analysis of electroencephalographic (EEG) epileptic seizure and brain dynamics with eye-open and eye-closed subjects during resting states

Abstract: ObjectiveEpilepsy is a neuronal disorder for which the electrical discharge in the brain is synchronized, abnormal and excessive. To detect the epileptic seizures and to analyse brain activities during different mental states, various methods in non-linear dynamics have been proposed. This study is an attempt to quantify the complexity of control and epileptic subject with and without seizure as well as to distinguish eye-open (EO) and eye-closed (EC) conditions using threshold-based symbolic entropy.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…The entropy was measured for control animals and epileptic animals for individual channels and showed that control animals had larger entropy values than the epileptic animals, also consistent with previous studies that entropy values are reduced for biological signals associated with death and aging (17,30,31,(33)(34)(35)(36). Table 1 shows the MSE profile analysis where healthy subject set O (Eye open) and epileptic ictal subjects depict highly significant results at all time scales 1 to 25.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The entropy was measured for control animals and epileptic animals for individual channels and showed that control animals had larger entropy values than the epileptic animals, also consistent with previous studies that entropy values are reduced for biological signals associated with death and aging (17,30,31,(33)(34)(35)(36). Table 1 shows the MSE profile analysis where healthy subject set O (Eye open) and epileptic ictal subjects depict highly significant results at all time scales 1 to 25.…”
Section: Discussionsupporting
confidence: 67%
“…The epileptic animals had lower entropy values (31,32) in their EEG signals, shown previously in case of interictal states to pathological and diseased biological systems (30,31,(33)(34)(35)(36)(37)(38). Lower entropy values also reveal that the signal has reduced complexity and previous findings also show that the brain was reflected due to abnormal behaviour in the rats (12,20,24,32,38,39).…”
Section: Discussionmentioning
confidence: 61%
“…In the past researchers used many complexity base measures to quantify the dynamics of physiological systems. Hussain et al (2017c) recently used Symbolic time series to detect and quantify the dynamics of epileptic seizure and distinguished between the healthy and epileptic subjects (ictal intervals) and interictal intervals (i.e. focal and nonfocal signals) and compared the results with multiscale sample entropy.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 depicts an example of one signal from each dataset used, described next: BONN. This database was collected at the Department of Epileptology, University of Bonn [ 33 ], and is a frequently used dataset found in many similar research studies [ 17 , 34 , 35 , 36 , 37 , 38 ]. The length of the records is 4097, with two classes of 100 time series each, corresponding to seizure-free and seizure-included electroencephalograms (EEGs).…”
Section: Methodsmentioning
confidence: 99%